Diagnosticidade da marca da loja frente à confusão do consumidor associada ao cenário multimídia e multicanal - Broilo, Patricia Liebesny (2018)
The increasing offer of products and services through multiple distribution channels and communication media characterizes the multimedia and multichannel scenario. This research aimed to deepen the understanding of consumer confusion associated with this scenario, considering that consumers tend to choose what and where to buy jointly. Specifically, based on the cue-diagnosticity theory, a thesis has been proposed that to overcome confusion and make a purchase decision, consumers tend to rely on the store brand revealing high diagnosticity of this cue in nowadays' scenario. Based on this proposition, a series of three experiments were carried on with consumers recruited through Mechanical Turk, to test six hypotheses. As a result, the first study demonstrated a negative effect of confusion on purchase intention, and a mediation of this effect by regret anticipation; the second study revealed the direct effect of confusion on purchase intention, as well as the indirect effect through regret anticipation, as being moderated by store brand reputation; the third study revealed that the same effects are observed when referring to a manufacturer's store brand. Among the contributions of this research, the following can be highlighted: a broad definition of consumer confusion associated with the multimedia and multichannel scenario; evidence that confusion impacts decision making during a buying experience; regret anticipation addressed as a mechanism that explains this effect; identification that consumers tend to consider the store brand reputation when it refers to a retailer as well as when it refers to a manufacturer selling directly to consumers; and the finding that store brand reputation can decrease the negative effect of confusion on purchase intention, revealing high diagnosticity of the store brand in light of consumer confusion. Academic and managerial implications are presented at the end of this report, along with opportunities for future research.